Does the market value M&A risk factor disclosures? Evidence from the involvement of investment bank advisors. Issue 1 (13th November 2021) - Xie, Fujiao; Wang, Tawei; Schochet, Sholom
Abstract: This paper investigates whether the market values risk factor disclosures in the context of mergers and acquisitions (M&A) and how the involvement of top‐tier investment banks affects the association. We complement previous research on risk factor disclosures by suggesting that the inter‐organizational relationship between companies and investment banks they hired in M&A transactions affects investors' perceptions of M&A risk factor disclosures. Specifically, we find that while M&A risk factor disclosures are positively related to the firms' market value, the involvement of a reputable investment bank advisor negatively moderates this relationship. Our research demonstrates that M&A risk factor disclosures are informative and the investment bank advisor as an intermediary would affect investors' perception of the acquirer's risk factor disclosures. The study provides implications for regulatory policies relating to risk disclosures, which should be of interest to regulators, investors, and managers.